Ответ:
1) (x+3y) / (x² - 9y²) = (x+3y) / [(x+3y)(x-3y)] = 1 / (x-3y)
2) a³ - 3a - 9a² - 25a² +5a² = a³ - 27a² + 2a = a(a² - 27a + 2)
3) (a² + 6ab + 96²) / (a² - 96³) = [(a + 48)² - 3·48·a + 3a²] / [(a - 96)(a² + 96a + 96²)]
= [(a + 48)² - 144a] / [(a - 96)(a + 48)²]
= (a - 96) / (a + 48)
4) a - a^3 - 9a^2 - 25a^2 +
Объяснение:
Будь добр(а) ответь как лудшый ответ
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
1) (x+3y) / (x² - 9y²) = (x+3y) / [(x+3y)(x-3y)] = 1 / (x-3y)
2) a³ - 3a - 9a² - 25a² +5a² = a³ - 27a² + 2a = a(a² - 27a + 2)
3) (a² + 6ab + 96²) / (a² - 96³) = [(a + 48)² - 3·48·a + 3a²] / [(a - 96)(a² + 96a + 96²)]
= [(a + 48)² - 144a] / [(a - 96)(a + 48)²]
= (a - 96) / (a + 48)
4) a - a^3 - 9a^2 - 25a^2 +
Объяснение:
Будь добр(а) ответь как лудшый ответ